Pengaruh Independensi, Komitmen Organisasi, Dan Ambiguitas Terhadap Kinerja Auditor Di Kantor Akuntan Publik Kota Padang (Jurnal Kendali Akuntansi, 2024)
This research aims to knowing the effect of Independency, Organizatinal commitment  and role ambiguity on Performance of Auditor in Public Accounting Firm, Padang City. This study uses a quantitative approach. The data collected from the study were based on interviews and questionnaire distribution with sampling technique is simple random sampling. Data analysis techniques in research. This is a linear multiple regression analysis with the help of computer SPSS program. Results this study can conclude that role ambiguity has a negatice effect on the performance of auditor,lndependency has a positive effect on the performance of auditor, and organizational commitment has no effect on performance of auditor  in Public Accounting Firm, Padang City